Sejarah Dakwah Nabi Muhammad pada Mayarakat Madinah: Analisis Model Dakwah Ukhuwah Basyariah dan Ukhuwah Wathaniyah - Azhar Azhar (UIN Sumatera Utara Medan, 2017)
In the course of the missionary history which has been exemplified by the Prophet Muhammad, especially in Medina, propaganda of prophets made significant progress. Especially after the passing of Piagam Madinah. The success of propagation of prophets in Medina can not be separated from the use of models of propaganda by the Prophet Muhammad. There are some interesting da'wah models for further analysis. The model of dakwah in question is the model of dakwah Ukhuwah Wathaniyah and Ukhuwah Basyariah. As for Ukhuwah Wathaniyah is one of the dakwah method that was propagated by Prophet Muhammad saw in order to live a sense of love and belonging to the state, which in this case is Medina. While Ukhuwah Basyariah is a method of propagation which is intensified by the Prophet Muhammad in order to foster the spirit of brotherhood on the basis of humanity. In the propagation model Ukhuwah Wathaniyah proclaimed by the prophet, the planting of love and owning the homeland becomes a very important thing. It was built with expeditions and military training to hone the power to protect the brother and the motherland. The Ukhuwah Basyariah is built by instilling the importance of the value of human equality before Allah Swt, although humans come from different ethnic, cultural, traditions, and religions. Thus, this model will make Muslims more tolerant to non. Islam Key words: Dakwah, Ukhuwah Wathaniyah, Ukhuwah Basyariah